2014
DOI: 10.3389/fcimb.2014.00169
|View full text |Cite
|
Sign up to set email alerts
|

Modeling early events in Francisella tularensis pathogenesis

Abstract: Computational models can provide valuable insights into the mechanisms of infection and be used as investigative tools to support development of medical treatments. We develop a stochastic, within-host, computational model of the infection process in the BALB/c mouse, following inhalational exposure to Francisella tularensis SCHU S4. The model is mechanistic and governed by a small number of experimentally verifiable parameters. Given an initial dose, the model generates bacterial load profiles corresponding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…During an infectious process when the immune system confronts numerous microbial cells, the random nature of the final phagosomal pH will result in some fraction of the infecting inoculum being controlled and possibly killed by initial ingestion, allowing antigen presentation. In this regard, the mean number of bacteria in the phagolysosomes and cytoplasm of macrophages infected with the intracellular pathogen Francisella tularensis exhibits stochastic dynamics (50), which in turn could result from the type of stochastic processes in phagolysosome formation noted here. Hence, chance in phagolysosomal pH acidification provides phagocytic cells with a mechanism to hedge their bets such that the stochastic nature of the process is itself a host defense mechanism.…”
Section: Discussionmentioning
confidence: 85%
“…During an infectious process when the immune system confronts numerous microbial cells, the random nature of the final phagosomal pH will result in some fraction of the infecting inoculum being controlled and possibly killed by initial ingestion, allowing antigen presentation. In this regard, the mean number of bacteria in the phagolysosomes and cytoplasm of macrophages infected with the intracellular pathogen Francisella tularensis exhibits stochastic dynamics (50), which in turn could result from the type of stochastic processes in phagolysosome formation noted here. Hence, chance in phagolysosomal pH acidification provides phagocytic cells with a mechanism to hedge their bets such that the stochastic nature of the process is itself a host defense mechanism.…”
Section: Discussionmentioning
confidence: 85%
“…The statistical characterization of the complete data set from 118 volunteers (112 febrile with measured IP, fever rise time, and near‐maximum fever) fills gaps in knowledge about early‐phase human tularemia unappreciated in previously published studies from portions of these data (Egan, Hall, & Leach, ; Jones, Nicas, Hubbard, Sylvester, & Reingold, ; Wood, Egan, & Hall, ). The statistical characterization of three parameters defining human fever profile are useful for comparisons to outputs of theoretical models of tularemia mechanisms, particularly IPs in animal models (Gillard, Laws, Lythe, & Molina‐París, ; Huang & Haas, ; Wood et al., ) and from human epidemiologic investigation (Egan et al., ). All of these studies considered F. tularensis strain Schu S4.…”
Section: Discussionmentioning
confidence: 99%
“…Gillard et al. () described theoretical mechanisms for tularemia progression in BALB/c mice administered 100 CFU by aerosol or nasopharyngeal routes for the first 48 hours of pathogenesis. Knowledge of the nature and magnitude of mechanisms driving pathogenesis in humans, nonhuman primates, and murine species would be needed for interspecies extrapolation of such modeling results in human health risk assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Francisella-infected macrophages promote a systemic anti-inflammatory reaction with high levels of TGF-β [125], with fatal consequences for the infected individual [126]. The first studies that highlighted the involvement of B lymphocytes in F. tularensis infection date back to the late 1990s, where it was found that B cells rather than antibodies were critical for protection against this bacterium [127].…”
Section: Francisella B-cell Infectionmentioning
confidence: 99%